Eel Business Development Strategy in PT Laju Banyu Semesta (Labas) - Hesti Indri Purwaty; Rina Oktaviani; Ono Suparno (Indonesian Journal of Business and Entrepreneurship (IJBE), 2018)
The objectives of this research were to illustrate the business model of PT Labas with the Business Model Canvas (BMC) approach, to develop the business development strategy of the company, and to describe the development of the company. This research used a descriptive analysis method. The analyzing tools used in this research included the Business Model Canvas (BMC) and Strength, Weakness, Opportunities, Threats (SWOT) analysis. The portraits of the existing nine elements of BMC of PT Labas describe the business processes that have been run by the company at this time. The SWOT analysis from these nine elements resulted in several alternative business development strategies for PT Labas. The strategies that can be undertaken by PT Labas management include operational improvement, core-plasma partnership with the enlargement partners, innovation & product quality improvement, market development, and business capital enhancement. BMC improvement is conducted by strengthening the elements of customer segment, channel, customer relationship, key resources, key activities, key partnership, and cost structure. The development of the BMC element provides changes to other elements.Keywords: eel (Anguilla spp.), PT Labas, BMC, strategy, business development